MENGEMBANGKAN KAPASITAS DAN KOMPETENSI SDM DI SEKTOR TEKNIK UNTUK MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 - Rini, Rini; Mahyudin Situmeang; Fider Lumban Batu; Nirwana Br. Bangun; Ridwan Nasution (Universitas Methodist Indonesia, 2023)
Industrial Revolution 4.0, which is characterized by digital technology and automation, has brought major changes to various industrial sectors, including the engineering sector. To face this era, it is necessary to develop the capacity and competence of human resources in the engineering sector so that they can adapt and utilize new technology optimally. This scientific work discusses the importance of developing human resource capacity and competency in the engineering sector to face the era of Industrial Revolution 4.0. It also describes strategies and programs that can be implemented to increase the capacity and competence of human resources, either through formal education, training or sustainable development programs. Points from research on HR Capacity and Competency Development in the Engineering Sector to Face the Era of Industrial Revolution 4.0: 1) The Importance of HR Capacity and Competency, 2) Challenges in HR Capacity and Competency Development, 3) HR Capacity and Competency Development Strategy, 4) Benefits of HR Capacity and Competency Development.